PERBEDAAN KETEBALAN MEDIA FILTRASI ARANG SEKAM PADI TERHADAP PENURUNAN KEKERUHAN PADA AIR BERSIH DI PT.X (Politeknik Kesehatan Kemenkes Bandung, 2021)
Clean water PT. X is sourced from groundwater. The value of turbidity in the clean water of PT. X after inspection is 189 NTU and exceeds the quality standard. Then the filtration process is carried out with rice husk charcoal filter media. Objective: to reduce the value of turbidity and to determine the difference in thickness of rice husk charcoal filter media with three variations, namely 30 cm, 40 cm, and 50 cm thickness. type of research: experimental research design with pretest-posttest without control. Population : all clean water used in PT. X. Sampling was done by grab sampling technique. Examination of turbidity values ​​in the laboratory, measurement of temperature and pH of clean water. Data collection tools: turbidy meter, water thermometer, and pH meter. The results: the average initial turbidity value in clean water is 189 NTU. The average turbidity value after the filtration process with rice husk charcoal media with a thickness of 30 cm got a value of 21.5 NTU with a percentage decrease, while at a thickness of 40 cm rice husk charcoal media got a value of 18.2 NTU with a decreasing percentage, then with The thickness of 50 cm rice husk charcoal media got a value of 14.6 NTU. Statistical test results with One-Way Anova test: p. value 0.001 < 0.05 so that there is a difference in the thickness of the rice husk charcoal filter media on the decrease in turbidity values. Suggestion: perform regular maintenance with backwash treatment at least once a day so that the retained dirt can be cleaned